LINEARITAS NILAI KETUHANAN DAN KEMANUSIAAN (STUDI KASUS PENGALAMAN SPIRITUAL WARIA DI PESANTREN WARIA AL-FATAH YOGYAKARTA) - Safri, Arif Nuh (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
The values of divinity and humanity are two aspects cannot be separated in living religion. The presence of God in every human being is a necessity and can undeniable. Meanwhile, people are also individuals who connected from other humans, because humans are social creatures. Therefore, faith must be proportional to the good deeds. Transgender as part of social life is also trying to prove them self as being godless creatures and social beings. The purpose is realized by establishing special schools transgender (pesantren waria). Pesantren founded in Yogyakarta became the fi rst transgender pesantren in Indonesia and even in the world. In the midst of the claim, transgender is a sinner ungrateful creature nature. Transgender showed up with his spiritual experience. Experiences are certainly cannot be equated with spiritual experiences that experienced by a kiyai, santri, scholars. They are regarded righteous in the eyes of society. Through this article, the author will try to give an idea of the spiritual experience of transgender in religion. Through this article, the author does not want to judge and claim their religious pattern of right or wrong. As well as this article, is expected to add a new discourse for the reader about the spirit and transgender spiritual experience. So, it can open a religious pattern that is more inclusive and open. Keywords: values of divinity, humanitarian values, transgender pesantren